State-owned entities and human rights : the role of international law - Barnes, Mihaela Maria, 1981- (Cambridge : Cambridge University Press, 2022)
The monograph focuses on the human rights challenges that are associated with the involvement of States in economic activities and on the role that international law has to play in addressing and understanding some of those challenges. State-owned entities are looked at through the lens of several topics of international law that have been found to hold particular relevance in this context, such as the concept of legal personality in international law, the process of normativity in international law, State immunity and State responsibility. The monograph shows how SOEs have had a significant role in shaping the evolution of international law and how, in turn, international law is currently shaping the evolution of State-owned entities. By focusing on State-owned or State-controlled business entities, rather than private corporations, the monograph aims to offer an alternative perspective on the challenges associated with corporations and human rights.
Introduction to the human rights dimension of state corporate ownership -- State-owned entities as a Sui generis 'participant' in international law -- State-owned entities and norm development in international law : international, regional and domestic approaches to regulation -- Fundamental change in international law : state immunity and state-owned entities -- The continued relevance of general international law : state responsibility and state-owned entities -- Concluding remarks.
Title from publisher's bibliographic system (viewed on 25 Nov 2021).
Keywords: Government business enterprises -- Law and legislation; International law and human rights; Government liability (International law); Liability for human rights violations